UPAYA MENANGGULANGI TRANSNATIONAL ORGANIZED CRIME DIBALIK BAYANG-BAYANG INDUSTRI JUDI DI KAMBOJA - Selvin Hadi Purba; Devina Yuka Utami; Alrin Tambunan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Transnational Organised Crime (TOC) is a complex crime because it involves actors from several countries and has a structured mechanism. One case that is currently rife is Indonesian citizens (WNI) who are victims of TOC behind the gambling industry in Cambodia. This happens because they are tempted by high salaries and lack of literacy about opportunities to work abroad. In reality, they do not work as expected, they are exploited and work under threat. Therefore, there is a need for prevention by the government so that these crimes do not happen again. One of the agencies that has the authority to prevent such crimes is immigration. Immigration can prevent people from leaving Indonesian territory for administrative or state security reasons. It is expected that the immigration function can be implemented optimally so that Indonesian citizens do not become victims of exploitation abroad. So that national security and citizen protection are maintained.